Coincidence time resolution of radiation detector based on 6×6 mm2 ToF SiPM detectors with different readout schemes - Li, Changyu; Li, Yuying; Xi, Jianbo; Xiang, Shitao; Hu, Kun (Frontiers in Physics, 2023)
Introduction: Nowadays, attention is growing on the Silicon Photomultipliers (SiPMs) detector for many applications, especially in nuclear medicine. In Positron Emission Tomography (PET) scanner, timing performance of a PET detector plays a significant role in image reconstruction. Methods: This work mainly aims at the processing of timing signal for the purpose of achieving a good timing performance. We applied a timing detector made up of a 3 × 3 × 10 mm3 LYSO crystal directly coupled with a large-size SensL SiPM with a sensitive area of 6 × 6 mm2. The standard output of the SiPM was used for energy calculation while the fast output was for timing pickoff. Three different readout configurations for fast timing signals were used for timing performance evaluation: 1) the recommended RF transformer-based readout, 2) the cascaded Common Emitter Amplifier (CEA), 3) the commercial RF amplifier. Results: Experiment results show that the best FWHM CTR values for the three were 228.3 ± 1.4 ps, 235.4 ± 1.1 ps and 231.1 ± 1.5 ps for the RF transformer-based, the CEA-based and the RF amplifier-based readout configurations respectively. The schemes based on the CEA-based and the RF amplifier-based configurations have a good uniformity at different trigger thresholds. Discussion: For practical application, the amplified timing signal based on the CEA circuit is more desirable because it is more feasible for trigger threshold selection in multichannel readout electronics system.